(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
Rural economy in Nigeria is worst hit with the erratic and unpredictable factors that affect agricultural practice which is the main livelihood of the rural farm households. Consequently, farmers are left with the option of sourcing other means of survival to cope with the hard times due to in consistent and seasonal distribution of income which characterize small farm holders in sub-Saharan African countries. This study investigates the factor influencing the livelihood income diversification among rural farm households in Osun state, Nigeria. Multi stage sampling techniques was employed to sample120 structured and pre-tested questionnaires from 120 rural farm households. Descriptive statistics and multiple regression analysis were used to analyze the data. The results of the descriptive statistics revealed that household heads of age range 50-60 years are 38.6% and about 40.70% had primary education while 26.30% had no education. About 98.31% of the rural households engaged in farming out of which 80.57% have farm size ranging between 1-3 hacters. Logit regression analysis shows that access to credit was positively significant (P<0.05) which implies that farmers that have access to credit were more likelihood to have income diversification. Age of the farmers was negatively significant (P<0.1). It connotes that the older the farmers the lesser the likelihood to income diversification. Income equivalent of household was positively significant (P<0.1). Access to electricity was positively significant (P<0.05). This implies that access to electricity increase farmer’s likelihood to income diversification. The off-farm income analysis shows that education and farm size were respectively negative and